Propozycja usprawnienia procesu planowania sprzedaży usług ubezpieczeniowych w sektorze MSP - Wojciel, Marcin (A Proposal of Improvement in Insurance Sales Planning for Small and Medium Enterprises, 2008)
The quality of territorial planning of sales in an insurance company can be improved by implementing a market model which includes variables reflecting the economic power of regions. A proposal described here leading to sales planning improvement is devoted to small and medium enterprises’ insurance market. The most convenient and useful variable which reflects differences among insurance demand in different regions is regional gross domestic product. The proposal shows the way how to implement this variable into sales planning to make it more accurate.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 27, s. 95-104